Review of the merits scale to become Secondary School Professor in Physical Education: Another medal for elite sport (Agora for Physical Education and Sport, 2021)
Access to the Secondary School Professors Staff has been paralyzed in the Autonomous Community of Castilla y León for over twenty years. It has been a long period in which Secondary School teachers have been restricted in their possibilities of internal promotion to a higher level in the professional field.Although the academic year 2019-2020 has meant a reactivation of the process of access to acquire the status of Professor in Secondary Education, the official call for applications has caused some criticism among different educational groups. Starting from a brief approach to the figure of the Professor, the main aim of this article is to review these criticisms and bring to light others related to the published scale of merits, in which elite sport regains a leading role in (Secondary) School Physical Education.
Keywords: Physical education; secondary school professor; high school